Spontaneous mutations affecting the host range of the B77 strain of avian sarcoma virus involve type-specific changes in the virion envelope antigen. - Zarling, D A (1977)
Previously it was shown that the host-range gene of the Bratislava strain of avain sarcoma virus (B77 virus) spontaneously mutates with a very high rate. The wild-type B77 virus called B77 virus-II, mutates either to virus that efficiently infects duck cells (B77 virus-III) or to virus that does not mutate to the ability to infect duck cells (B77 virus-I) (Zarling and Temin, 1976). No significant differences in either the virion envelope glycoproteins or other major virion proteins were detected by sodium dodecyl sulfate-polyacrylamide gel electrophoresis. However, pseudotypes of B77 virus-I with proteins of a transformation-defective mutant of B77 virus-III formed foci efficiently in duck cells. An alteration in the envelope protein of B77 virus-I was demonstrated by experiments in which B77 firus-I was fused into duck cells with UV-irradiated Sendai virus and formed foci. Neutralization experiments further demonstrated that B77 virus host-range mutants have altered type-specific envelope antigens. Thus, the spontaneous mutations in the host-range gene of B77 virus involve changes in the type-specific virion envelope antigen.